Service-Learning in Costa Rica and Indonesia - Williams, David D.; Eiserman, William D. (Education Policy Analysis Archives, 1997)
Calls are increasingly sounded for universities to better address their communities' and students' needs through service, as well as research and teaching. This article invites policy makers to re-examine university service, research, and teaching responsibilities by reflecting on roles service-learning plays in universities in Indonesia and Costa Rica. We conclude that service-learning plays a critical role and a key to expanding service-learning for students and understanding the utility of such a policy change is increased faculty involvement. Until more faculty explore the "why" and "how" of service-learning, research and teaching will dominate the university agenda.